How to find the Ariadne's thread in the labyrinth of salvage treatment options for metastatic colorectal cancer?. (June 2014) - Bronte, Giuseppe; Rolfo, Christian; Peeters, Marc; Russo, Antonio
Abstract : Since a chance for cure was found out in metastatic colorectal cancer (mCRC) patients undergoing a resection of liver and lung metastases, high tumor shrinkage by chemotherapy regimens and their combination with targeted agents have been addressed in potentially resectable mCRC. However, most mCRC patients cannot reach this opportunity because of tumor burden or metastatic sites. For these patients a salvage systemic therapy could be offered to prolong survival. To date, a huge number of clinical trials provided some evidences for the achievement of this goal. A lot of chemotherapeutic regimens in combination with biological therapies are now available. We tried to propose a simple way to choose the best options and to plan an optimal sequence of treatments. This tool could help the oncologists worldwide to better and easily manage mCRC patients who need salvage systemic therapy.